Antioxidant activity of methanol extract of Tinospora crispa and Tabernaemontana corymbosa - Heida Nadia Zulkefli,; Jamaludin Mohamad,; Nurhayati Zainal Abidin, (Universiti Kebangsaan Malaysia, 2013)
Tinospora crispa and Tabernaemontana corymbosa have been used traditionally to treat fever, diabetes, rheumatism and sinusitis. The objective of this study was to evaluate the antioxidant activity of Tinospora crispa and corymbosa. The presence of apigenin and magnoflorine was detected using LCMS/MS in crispa (Patawali) whereas appararicine, voafinine, conodusarine, conodurine, voacamine and voacangine were detected in corymbosa (Susur kelapa) methanol extract. The stem extract of crispa showed high antioxidant activity in the following order: DPPH radical scavenging, reducing power and metal chelating assay (98.8%, 0.957, 81.97%) than corymbosa of leaves (90.04%, 0.652, 69.64%), stem (82.78%, 0.819, 36.70%) and root extracts (63.25%, 0.469, 51.56%), respectively. The high antioxidant activity in the stem extract of crispa is due to the presence of apigenin and magnoflorine. The high antioxidant activity in Tabernaemontana corymbosa extract is due to its high phenol contents. There were significant linear positive correlation (r=0.788, p<0.001, r2=0.621) between the total phenolic content and DPPH free radical scavenging assay in the crude extracts of Tinospora crispa and corymbosa. Meanwhile, a significant moderate positive correlation was observed between the total phenolic content and ferric reducing power assay (r= 0.556, p<0.05, r2= 0.309). However, there was no significant difference in the correlation coefficient of total phenolic content and metal chelating assay.